2011
DOI: 10.1038/sc.2011.126
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lithium carbonate treatment of chronic spinal cord injuries: a double-blind, randomized, placebo-controlled clinical trial

Abstract: Study design: Lithium has attracted much attention as a neuroregenerative agent for spinal cord injury in animal models. We hypothesized that the lithium can be beneficial to patients with spinal cord injury. The safety and pharmacokinetics of lithium has been studied in our earlier phase I clinical trial, indicating its safety. This is a phase II clinical trial to evaluate its efficacy on chronic spinal cord injury patients. Objectives: The aim of this study was to investigate the efficacy of lithium on chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 41 publications
1
41
1
Order By: Relevance
“…25 Another neuroregenerative agent, lithium carbonate, was investigated, but it did not improve the neurological outcome in patients with SCI. 26 Many studies have shown the effects of exercise training on neuronal plasticity. Exercise improved gait and led to neurological recovery, 27 probably by enabling the intrinsic neuronal circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…25 Another neuroregenerative agent, lithium carbonate, was investigated, but it did not improve the neurological outcome in patients with SCI. 26 Many studies have shown the effects of exercise training on neuronal plasticity. Exercise improved gait and led to neurological recovery, 27 probably by enabling the intrinsic neuronal circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3β inhibitors, particularly the clinical drug lithium, have been reported to be beneficial after CNS injuries. Lithium has been studied in phase I/II clinical trials to evaluate its efficacy on chronic SCI patients (Yang et al, 2012). …”
Section: Cspg Inhibition and Axon Regenerationmentioning
confidence: 99%
“…HP184, a sodium/potassium channel blocker has been tested in a phase 2 clinical trial, but no official data have been released (NCT00093275). Lithium has been shown to act as a neuroregenerative agent in animal models and was tested in phase 1 and 2 clinical trials (NCT00431171, NCT00750061), but no neurological benefits were observed [125]. Notwithstanding the series of failed clinical trials, there are many ongoing trials that provide patients with some hope for novel treatment options [126].…”
Section: Clinical Trials In the Spinal Cordmentioning
confidence: 98%